Canine Leptospirosis: Clinical and Ultrasonographic Assessment in South Gujarat - M Parmar, Saurabh; D Patel, Manish; A Vala, Jignesh; A Mehta, Sudhir; C Parmar, Hitesh; Chand Koli, Ramesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Leptospirosis is a severe spirochetes infection in dogs that can cause significant damage to vital organs, particularly the liver and kidneys and may lead to life-threatening complications. This study was aimed to assess occurrence of leptospirosis in dogs along with associated haemato-biochemical and ultrasonographic changes. Over a period of two years, 195 cases (3.50%) were suspected out of total 5566 dogs registered for medical treatment. Among confirmed 30 cases (15.38%), majority of affected dogs (60%) were between 1-6 years old and males (70%). On ultrasonographic evaluation of confirmed cases of canine leptospirosis, more than 80% cases exhibited kidney to aorta ratio greater than 9. Pyelectasia (80%), medullary rim sign in the kidney (70%) and hypoechoic liver parenchyma (60%) were also observed during ultrasonography. Haematological analysis revealed elevated mean total leukocyte counts (26790 cells/µL) along with neutrophilia (80.4±10.04%) and mild anaemia (11.33±3.19 g/dL). Serum biochemical analysis showed elevated mean serum AST (71.28±47.37 IU/L) and ALT (86.28 ±53.26 IU/L) along with hypoalbuminaemia (
Keywords: Canine; Leptospirosis; Medullary rim sign; Pyelectasia; Ultrasonography